Digital-Based Learning in English Folklore Lectures for Islamic Higher Education - Muhammad Yunus; Sitti Rahmawati; Muliadi Muliadi (ELT Worldwide: Journal of English Language Teaching, 2022)
Digital technology has begun to permeate all spheres of society, including education, particularly higher education. This research is concerned with investigating the need for digital-based learning materials in the folklore course at the Faculty of Letters, Indonesian Muslim University. This study employs a qualitative descriptive approach by gathering data through questionnaire. The samples consisted of 5 lecturers and 50 students with a total of 55 samples that were given a questionnaire to which they have given consent to participate. According to this study, among other findings, students were becoming tired with printed educational materials. Students could have a unique experience with digital teaching resources, which can aid both lecturers and students in learning. Using the application Focusky, digital teaching materials containing historical folklore elements could be produced as a learning material. Digital teaching materials designed as presentation media with animations and 3D transition effects that zoom in and out to capture the attention of students. Focusky for courses in folklore seemed to have a very high level of practicability. The design or presentation of digital teaching materials and the content included within them are enough and adequate for innovative learning. Furthermore, based on the responses of lecturers and students to the digital teaching materials, the practicality of Focusky was rated as very good, and there were no significant challenges for lecturers and students when utilizing digital teaching materials for the history of folklore in learning.